Membangun Kembali Kepercayaan Publik: Inovasi Kewirausahaan dan Internalisasi Nilai-Nilai Dakwah dalam Perbankan Syariah di Era Disruptif - Siti Trizuwani; Cecep Castrawijaya (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
In this era of digital disruption, Islamic banks face significant challenges in maintaining public trust. Despite growth in assets and market share, many believe that Islamic banks operatein much the same way as conventional banks, while financing marginsare often considered higher than conventional bank interest rates. This perception contributes to low public trust, declining interest in saving, and public hesitation in using Islamic financing products. This study aims to explore how entrepreneurialinnovation and internalization of da'wah values canbe strategies to rebuild public trust in Islamic banks. Using the library research method, this study analyzes secondary data from scientific journals, reports, andliterature related to Islamic banking, digital transformation, and Islamic managerial ethics Islam. The results of the study show that the integration of dakwah princip lessuch as transparency, fairness, and ethical management in entrepreneurial practicesand digital innovation can strengthen public trust andincrease the competitiveness of Islamic banks. This study provides theoretical and practical insights for Islamic banks to align digital innovation and business strategies with core Islamic values, there by supporting financial sustainability and social legitimacy.